Computing the Performance Measures in Queueing Models via the Method of Order Statistics - Yousry H. Abdelkader (Journal of Applied Mathematics, 2011)
This paper focuses on new measures of performance in single-server Markovian queueing system. These measures depend on the moments of order statistics. The expected value and the variance of the maximum (minimum) number of customers in the system as well as the expected value and the variance of the minimum (maximum) waiting time are presented. Application to an M/M/1 model is given to illustrate the idea and the applicability of the proposed measures.